Study of Local Correlations of the Simultaneous wind Speed-irradiance Measurements Using the Time Dependent Intrinsic Correlation Method - Calif, Rudy; Schmitt, Fran¸cois; Huang, Yongxiang (Journal of Applied Nonlinear Dynamics, 2026)
Renewable resources such as atmospheric wind speed and global horizontal irradiance, possess huge fluctuations over a large range of spatial and temporal scales, indicating their nonlinear and nonstationary properties. In this study, the multiple scale dynamics and the correlations between simultaneous time series are analyzed using EMD (Empirical Mode Decomposition) based methods, particularly appropriate for such time series. We consider simultaneous wind speed-global horizontal irradiance measurements, sampled at 1 hour over a period of three years, from 2010 to 2013, at Guadeloupean Archipelago (French West Indies) located at 16°15'N latitude and 60°30'W longitude. After EMD decomposition of both time series, power laws are observed in the Fourier and Hilbert spaces over a broad range of frequencies. Furthermore, we investigate their local correlations using the Time Dependent Intrinsic Correlation method (TDIC). The time evolution and the scale dependence of their correlation are determined at different time scales and for different intrinsic modes functions. The estimation of TDIC have highlighted strong correlations for all the time scales, particularly strong negative correlations between both time series for mean periods 2h≤Tm